2009
DOI: 10.1002/ab.20317
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between psychopathy and indirect aggression use in a noncriminal population

Abstract: Psychopathy has long been associated with increased use of direct aggression and violence, especially among male inmates. Little research has, of yet, considered the relation between psychopathy and indirect forms of aggression. The current research sought to investigate the relationship between psychopathy and indirect aggression in a noncriminal sample. The results indicated that there was a strong relationship between psychopathic traits and indirect aggression, with strong correlations between indirect agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 41 publications
(73 reference statements)
3
23
0
Order By: Relevance
“…Despite its practical and effective quality of assessing traits of interests, this method may be prone to response bias. Although psychopathic traits, aggression, and moral judgment have been found to be significantly related to socially desirable responding (Warren, 2009), the same study has found that socially desirable responding did not have a significant impact on the associations between psychopathy, aggression, and empathy. Nonetheless, future studies could use other measures, such as utilizing role-play in the laboratory or other behavioral paradigms to replicate and build upon this research.…”
Section: Discussionmentioning
confidence: 85%
“…Despite its practical and effective quality of assessing traits of interests, this method may be prone to response bias. Although psychopathic traits, aggression, and moral judgment have been found to be significantly related to socially desirable responding (Warren, 2009), the same study has found that socially desirable responding did not have a significant impact on the associations between psychopathy, aggression, and empathy. Nonetheless, future studies could use other measures, such as utilizing role-play in the laboratory or other behavioral paradigms to replicate and build upon this research.…”
Section: Discussionmentioning
confidence: 85%
“…Indeed, social desirability bias has been shown to affect self-report assessment of psychopathy, empathy, and moral judgements (Warren, 2009), but the same study also showed that social desirability bias does not significantly impact the association between psychopathy and moral judgements about aggressive behaviours. Nonetheless, future studies can rely on more objective measures like skin conductance activity to assess the emotional profile of psychopathy when making moral judgements.…”
Section: Limitationsmentioning
confidence: 94%
“…Both impulsive and premeditated violence represent a lack of deliberation or concern for potential consequences, but rather than being limited to acute lapses in behavioral control, for psychopaths this also impinges on long-term planning and goal-oriented behavior. In non-incarcerated samples, conceivably less prone to physical violence, these deficits remain apparent, represented by forms of indirect, relational aggression (Czar et al 2011; Warren and Clarbour 2009). …”
Section: Predicting Violent Outcomesmentioning
confidence: 99%